Sexual difference : masculinity and psychoanalysis - Frosh, Stephen (Routledge, 1994)
This critical exploration of issues of gender in psychoanalysis acknowledges and updates the complexity of theory and writing in this area, particularly the way sexual differences can only be thought about from a gendered position.